Clearing the Air: A Qualitative Investigation of Genetic Counselors' Experiences of Counselor‐Focused Patient Anger. Issue 5 (5th February 2015) - Schema, Lynn; McLaughlin, Michaela; Veach, Patricia McCarthy; LeRoy, Bonnie S.
Abstract: Patient anger is challenging for healthcare professionals to manage, particularly when it is directed at them. This study comprises the first in‐depth investigation of genetic counselors' experiences with patient anger. Using a brief survey and interview methods, this study explored prevalence and context of patient anger directed at the genetic counselor, how genetic counselors manage patient anger directed at them, and possible thematic differences due to genetic counseling experience. Individuals enrolled in the National Society of Genetic Counselors (NSGC) listserv were invited to participate in a study of their experiences with patient anger directed at them. A majority of survey respondents (95.7 %, 243/254) reported experiencing patient anger directed at them, and 19.4 % reported having feared for their safety because of patient anger. Twenty‐two survey respondents were purposively selected to participate in individual interviews. Inductive and cross case analysis yielded prevalent themes concerning patient triggers for anger, including bad news, logistical mishaps, and perceived counselor characteristics. Interview results further suggest unaddressed patient anger negatively affected patient and counselor emotional well‐being and hindered genetic counseling goals. Prevalent challenges included genetic counselor attempts to accurately recognize, understand, and effectively manage patient anger without taking it personally. Commonly recommended strategies for addressing anger were empathy (i.e., understanding origins of patient anger), anticipating and acknowledging anger, maintaining personal, professional and legal protection, and debriefing with colleagues. Themes were quite similar across counselor experience levels. The findings underscore the importance of training and continuing education regarding patient anger. Additional findings, practice implications, and research recommendations are presented.